Punished mischiefs of González and Ipinza, the counter-exemplary friends of Hijo de ladrón - Valenzuela Medina, Daniel (Revista Chilena de Literatura, 2021)
In this article I propose a critical reading of the gender and class constitution of two male characters present in Manuel Rojas’ Hijo de ladrón (1951). The characters González and Ipinza, along with being two counter-exemplary male types, are represented using typical aesthetic resources of comic literature, understood in the variant defined by Bakhtin. This updated comic dimension draws from archaic sources and allows the narrator (one of the refracted voices of the artist-author) to carry out an ironic and critical operation in which political elements that point to a particular ethic of the characters can be perceived. The ethics, the way of acting and giving of the male characters allow a reading that understands their particularities as metonymies and allegories of referential historical male types and the functioning of the patriarchal, capitalist, and liberal framework of the early South American 20th century (Chile and Argentina).